Critical Role of Micronutrient in Crop Production: A Review - Wedajo, Mulisa Abdi (Food, Agriculture and Natural Resources - NETWORKS, 2025)
In developing countries, crop production and productivity faces significant problems, among which soil nutrient availability is crucial. While primary plant nutrients nitrogen (N), phosphorus (P), and potassium (K) have given considerable attention, on the other case; deficiency of micronutrients and secondary nutrients is becoming more widely acknowledged as a major limiting factor for obtaining optimal crop yields and nutritional quality. This review highlights information on the importance of micronutrients (B, Cl, Cu, Fe, Mn, Mo, Ni, Zn) in agriculture crop production, focusing the growing prevalence of deficiencies due to continuous cropping, soil erosion, nutrient leaching, and unbalanced nutrient application in cropping system. Particularly focus given to the situation in Ethiopia and Sub-Saharan Africa, where exhibit multi-nutrient deficiencies are widespread in soil degraded, its impacts not only reductions of crop yields but also contributing to human malnutrition through poor crop dietary quality. Based on the evidence provided, addressing micronutrient limitations, crop yields can be greatly increased, nutrient use efficiency can be improved, and human health problems associated with micronutrient deficiency may be mitigated by using balanced nutrient management systems that combine macro- and micronutrients. The review provided the need for increasing research, targeted soil fertility improvements, and policy focus on micronutrients to ensure sustainable crop productivity and food security.